2019
DOI: 10.1093/rb/rbz027
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced angiogenesis by the hyaluronic acid hydrogels immobilized with a VEGF mimetic peptide in a traumatic brain injury model in rats

Abstract: Angiogenesis plays an important role in brain injury repair, which contributes to the reconstruction of regenerative neurovascular niche for promoting axonal regeneration in the lesion area. As a major component of developing brain extracellular matrix, hyaluronic acid (HA) has attracted more attention as a supporting matrix for brain repair. In the present study, HA-KLT hydrogel was developed via modifying HA with a VEGF mimetic peptide of KLT (KLTWQELYQLKYKGI). The characterization of the hydrogel shows that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…TGF-β could promote mitosis and osteogenic differentiation of osteoprogenitor cells [ 29 ]. VEGF was a key player that regulated the recruitment, survival and activity of endothelial cells, osteoblasts and osteoclasts [ 30 , 31 ]. Figure 3A−C shows that the composite gels containing different concentrations of PRP and LyPRP were soaked in culture medium to simulate the in vitro release behavior of these factors.…”
Section: Resultsmentioning
confidence: 99%
“…TGF-β could promote mitosis and osteogenic differentiation of osteoprogenitor cells [ 29 ]. VEGF was a key player that regulated the recruitment, survival and activity of endothelial cells, osteoblasts and osteoclasts [ 30 , 31 ]. Figure 3A−C shows that the composite gels containing different concentrations of PRP and LyPRP were soaked in culture medium to simulate the in vitro release behavior of these factors.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the microvascular structures marked by an endothelial marker such as CD-31 can be performed through fluorescence microscopy (Costa-Almeida et al, 2015), epifluorescence microscopy (Weinandy et al, 2014), confocal laser scanning microscopy (Costa-Almeida et al, 2015;Dos Santos et al, 2019;Heller et al, 2020;Heller et al, 2016;Ren et al, 2014;Unterleuthner et al, 2017;Xiao et al, 2015), two-photon laser scanning microscopy (TPLSM) (Kniebs et al, 2020;Kreimendahl et al, 2017;Samal et al, 2015;Weinandy et al, 2014), or scanning electron microscopy (SEM) (Lu et al, 2019;Samal et al, 2015;Shen et al, 2017).…”
Section: Immunolabelingmentioning
confidence: 99%
“…The functional motif KLT (KLTWQELYQLKYKGI) is a VEGF mimetic peptide and could combined to VEGF receptors and improve the migration, proliferation, and tubulogenesis of ECs [180]. Lu et al modified hyaluronic acid hydrogels with KLT and demonstrated that the HA-KLT hydrogel could improve the spreading, and proliferation of HUVECs in vitro and promoted angiogenesis in vivo [181]. The glycine-histidine-lysine (GHK) peptide is a fragment of osteonectin, and could promote the secretion of VEGF from MSCs in alginate hydrogels [182].…”
Section: Small Moleculers-based Approaches For Vascular Networkmentioning
confidence: 99%